2005
DOI: 10.1007/s10143-005-0407-4
|View full text |Cite
|
Sign up to set email alerts
|

Success of endoscopic third ventriculostomy in children less than 2 years of age

Abstract: Current literature reveals different opinions about the effectiveness of endoscopic third ventriculostomy in the treatment of hydrocephalus in children less than 2 years of age. Performing a retrospective evaluation of our own experience in this age group, we aimed to contribute to the growing data on the controversial issues related to this procedure in children. In a series of 97 endoscopic third ventriculostomy procedures, 25 were performed in children less than 2 years of age as an initial treatment for hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…1,2,4,6,7,9,11,16,18,20 Recently, we used confounder-adjustment techniques (propensity score modeling) to compare the failure rate of ETV versus shunt placement. 13 We found that, once adjusted for confounders, ETV is associated with a higher initial failure rate, but, over time, the failure rate becomes lower than that associated with shunt placement.…”
mentioning
confidence: 99%
“…1,2,4,6,7,9,11,16,18,20 Recently, we used confounder-adjustment techniques (propensity score modeling) to compare the failure rate of ETV versus shunt placement. 13 We found that, once adjusted for confounders, ETV is associated with a higher initial failure rate, but, over time, the failure rate becomes lower than that associated with shunt placement.…”
mentioning
confidence: 99%
“…Data from the literature suggest that the clinical response to ETV in adult patients with obstructive hydrocephalus is different from that in children, and the differences are secondary to the age at onset of hydrocephalus, CSF dynamics, and changes in brain viscoelastic properties 8,11,22) . Rates of success reported for ETV in patients 2 years old and younger vary from 0 to 83.3% with a mean of 47.8%, which is significantly lower than the success rate in older children 2,3,6,9,10,[12][13][14]16,[18][19][20][21]24,28,29) . However, when evaluating success rates of secondary ETV, Marton et al 22) reported that age does not have a statistically significant effect, which is also reflected by our data.…”
Section: Discussionmentioning
confidence: 84%
“…Historically, endoscopic third ventriculostomy (ETV) always seemed to be a promising technique and can be considered nowadays a standard procedure for obstructive hydrocephalus 6,7 . However, data published in the medical literature is both extensive and conflicting when they come to the role of patients' age and etiology of the hydrocephalus in the success rate (SR) of endoscopic procedures 6,[8][9][10][11][12][13][14][15][16][17][18] . In this study, we present the results of neuroendoscopic operations performed in children during the past ten years in the same institution.…”
mentioning
confidence: 99%